Inhibition of Fibrinogen Binding and Surface Recruitment of GpIIb/IIIa as Dose-Dependent Effects of the RGD-Mimetic MK-852 - Wittig, Kathrin; Rothe, Gregor; Schmitz, Gerd (Thrombosis and Haemostasis, 1998)
Conformational activation of platelet GpIIb/IIIa which is coupled to increased affinity for binding of soluble fibrinogen is an important step in platelet aggregation. Antibodies, peptides, and small molecules which antagonise fibrinogen binding, therefore, have been developed as a new class of potent anti-aggregatory compounds. The binding of these artificial ligands, however, similar to fibrinogen binding may also stimulate platelet adhesion and degranulation. Therefore, in this study effects of MK-852, a cyclic hexapeptide based on the RGD-template, on the platelet phenotype were analysed by whole blood flow cytometry. MK-852 already in the nanomolar range completely inhibited the surface binding of fibrinogen to ADP or TRAP-6 stimulated platelets. In the micromolar range, MK-852 induced an up to four-fold increase of GpIIb/IIIa surface expression in the absence of increased P-selectin expression. In conclusion our results suggest that the selective surface recruitment of GpIIb/IIIa may be a side effect of exposure to RGD-analogues which occurs at concentrations well above inhibition of fibrinogen binding.